Ba[Mg2Al2N4]Eu2+ phosphor for enhancing the optical quality of the 6600K CPW-LEDs - Van-Duc Phan; Duy-Hung Ha; Minh Tran; Tran Thanh Trang (Universitas Ahmad Dahlan, 2019)
Compared with conventional lamps, LED-based light sources have a superior lifetime, efficiency, and reliability, which promise significant reductions in power consumption and pollution from fossil fuel power plants. The main purpose of this paper is proposed and investigated the effect of the concentration of Ba[Mg2Al2N4]Eu2+conversion phosphor on the CCT deviation (D-CCT) and lumen output (LO) of the 6600 K conformal-packaging white LEDs (CPW-LEDs). For this purpose, we used the Light Tools and Mat Lab software to investigate this problem. From the research results, we can state that the concentration of the red phosphor crucially influenced on the optical quality of the 6600 K CPW-LEDs. The D-CCT can be decreased from 4700K to 2500K, and the LO can be increased from 600 lm. to 1200 lm. This research can provide the new recommendation for LEDs industry at this time.